Media content, sentiment and emerging market futures returns. Issue 7 (7th February 2023) - Pok, Wei Fong; Kabir, M. Humayun; Young, Martin
ABSTRACT: The paper attempts to capture the sentiment derived from routine financial news and outlines the impact of the media content on the main index futures contracts of Hong Kong and Singapore. News factors are generated from routine financial news, but pessimistic market sentiment factors are more prevalent. High pessimistic news factors predict lower returns for the same day, and the returns start to reverse two days after the news for Hong Kong and Singapore markets. The finding is consistent with the sentiment theory. There is a significant reversal in returns, and the reversal in returns offsets the initial changes entirely. The bad news factor does not seem to work as a proxy for trading costs. The sub-sample results are similar to the whole sample. We also find the significant impact of U.S. news sentiment on news factors, futures return, and open interests in both markets. Trading strategies based on bad news factors generate economically significant returns when trading costs are considered.